Secure smart home automation and monitoring system using internet of things - Mohamed Khudhair Al-Gburi; Laith Ali Abdul-Rahaim (Institute of Advanced Engineering and Science, 2022)
As a result of the rapid increase in the number of users in internet of things (IoT) technologies, IoT becomes one of the most important technologies that play an important and essential role in various areas of human life, it provides service over 24 hours. In this paper, the proposed system relies on the implementation of a set of sensors for the Internet of things, which accomplish tasks inside the home automation, for example, controlling the main door, boiler and lock, as well as the ability to control lighting and air, internal temperature sensors, it based on the Arduino, to collect multimedia data, and remote-controlled sensors. The proposed system provides an efficient way to control and monitor the various devices in the home for security and safety purposes, and through sensors that rely on wireless technologies. The results show the abnormal alarm notification for heathcare/security purposes with the distance as 27 cm, smoke carbon monoxide on indoor air quality as 10211 degree Co as 6256 degree, Liquefied petroleum gas as 5097 degree, the delayed 3.4 ms and network latency as 0.0012 seconds of alarm notification with long distance as 60 m and high packet delivery ratio as 98.7%.